Making strategy at a Malaysian higher education Institution - Abdul Rahman, Shukran; Abdullah, Nur Anisah (IACSIT Press, 2011)
Malaysia is working towards transforming into a knowledge-driven economy where the generation and the utilization of knowledge contribute significantly to economic growth and wealth creation.Knowledge being singled-out as one of the key factor in driving growth and creating value. This notion has an expansive implication on how industry, academia and government must now work closer to make active contribution. Universities are now driven to find their way to better deliver. Drawing upon Mintzberg’s five definitions of strategy: plan, ploy, pattern, position and perspective [1], this paper reviews the elements of strategic planning in the context of a higher education institution in facilitating their strive to deliver in responding to those emerging demands. It also demonstrates how the Balanced Scorecard framework can potentially help structure a more comprehensive thought-through process in shaping strategies. It concludes with a set of guidelines for strategy making.